Potencial prebiótico do liofilizado da polpa de xique-xique (Pilosocereus gounellei (F.A.C. Weber) Byles & Rowley) sobre a microbiota colônica humana - Silva, Sabrina Radames Ferreira da (2024)
Pilosocereus gounellei (F.A.C. Weber), a plant specie popularly known as xique-xique, is a cactaceae characterized as an unconventional food plant (PANC) native to the Caatinga biome, which has been studied in relation to its nutritional properties and as a source of bioactive compounds, including those with prebiotic properties. The aim of this study was to evaluate the prebiotic potential of freeze-dried xique-xique pulp on the human colonic microbiota of healthy individuals. To this end, a freeze-dried powder was prepared from the xique-xique pulp (FDPg), and analyses were carried out to determine its nutritional composition and physicochemical parameters, followed by in vitro gastrointestinal digestion. The FDPg digested was subjected to a fermentation test with human fecal inoculum and metagenomic analyses (16S rRNA sequencing) and monitoring of metabolic activity indicators (pH, sugars, organic acids, phenolic compounds, and metabolomics) and antioxidant activity were carried out. The analyses were carried out on the freeze-dried raw sample and on the fermented medium over time during 48 h of in vitro colonic fermentation. The experiments were carried out in triplicate, and the results are expressed as mean ± standard deviation. The FDPg had an acidic pH, a high content of dietary fiber, mainly insoluble fiber, sugars, organic acids, and phenolic compounds in its composition, with antioxidant capacity. Throughout colonic fermentation, the FDPg generally caused desirable changes in the bacterial groups that make up the human intestinal microbiota, with an increase in the relative abundance of bacteria beneficial to intestinal health, such as Mitsuokella, Bacteroides, Megasphaera and Acidaminococcus, and a decrease in the relative abundance of bacteria considered to be non-beneficial, such as Succinivibrio, Citrobacter, Escherichia-Shigella, Faecalibacterium and Blautia. In addition, FDPg stimulated the metabolic activity of the intestinal microbiota throughout colonic fermentation, reflected by a reduction in the pH values, production of short-chain fatty acids, production of phenolic compounds (e.g., epicatechin, epigallocatechin, and procyanidin B2) and maintenance of antioxidant capacity. This way, FDPg can be characterized as an ingredient with prebiotic properties that can be used to produce innovative products with functional properties and high added value.